Resistance and Hope in a Teacher's Job - Salmerón Alpízar, Xinia (2004)
In one of the national newspapers, I found a new article on Costa Rican education. I read it with interest and at the same time with concern. I did so with interest because, for me, education is not only a subject on which we should have an opinion, but because it is part of my life of my daily concerns. Education, being the field of my professional activity, absorbs me and allows me to have a very close communication with others.